PREVALENCE AND ANTIBIOGRAM OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS FROM VARIOUS CLINICAL SAMPLES IN RURAL TEACHING HOSPITAL -ANDHRA PRADESH - DR.RAJIVE KUMAR SUREKA; DR.A.J NANDESHWAR (International Journal of Pharma and Bio Sciences, 2014)
MRSA (Methicillin-resistant Staphylococcus aureus ) is a major causative agent for hospital acquired infections.Prevalence of MRSA is increasing and leading to increased mortality,morbidity and cost of treatment due to increased number of days of hospital stay.so present study was conducted .various clinical samples such blood urine,sputum,body fluids,BAL,wound swab and pus were collected under aseptic precautions and innoculated on bllod agar,MacConkeys agar and incubated overnight 370c,once the growth was observed, bacterial identification was done by standard biochemical test and special test such as coagulase.mannitol fermentation confirms satphylococcus aureus .MRSA detuction done as per CLSI (Clinical and Laboratory Standards Institute ) guidelines by cefoxitin disc diffusion method.Antibiotic sensitivity testing done by modified kirby baures disc diffusion method.out of 1224 samples, 371 were identified as staphylococcus aureus out of which 128 were found to be MRSA(methicillin resistant Staphylococcus aureus).prevalence of MRSA was 34.5%.Incidence and prevalence of MRSA is increasing at alarming rate,most of MRSA were found to be resistant ot commonly used antibiotics.Antibiotic policy and hand wash hygine are important to control hospital aquired infection by MRSA.